An improved electrochemical model for strain dependent electrochemical polarization and corrosion kinetics. (April 2021) - Wei, B.; Legut, D.; Sun, S.; Wang, H.T.; Shi, Z.Z.; Zhang, H.J.; Zhang, R.F.
Abstract: To systematically reveal the correspondence between surface properties and corrosion behaviors under mechanical conditions, an improved Butler-Volmer (IBV) electrochemical model is proposed by introducing the strain effects on electrochemical polarization through the scaled strain energy. Under mechanical straining, the three critical physical parameters i.e., surface energy, work function and strain energy, may be changed synergistically, which would consequently modify the exchange current density and equilibrium potential for the anode polarization curves. Taking two representative metals of Mg and Zn as a demonstration, it reveals that both tensile and compressive strain would contribute to the corrosion rate by lowering the activation energy barrier, in agreement with previous experimental observations. The improved model opens an alternative way to quantify the relationship between surface properties and corrosion behavior via intrinsic materials properties, which is beyond the normal design rules empirically based on either surface energy or work function alone. Graphic abstract: Unlabelled Image Highlights: An improved Butler-Volmer model is presented to reveal the correspondence between surface properties and corrosion behaviors under straining. The basal planes for pure Zn and Mg show much lower corrosion/degradation rates than the prism planes. Both tensile and compressive strains can promote the corrosion/degradation of Zn and Mg.